Lathrolestes verticalis Brischke 1871 ... - Reshchikov, Alexey (Zenodo, 2015)
Lathrolestes verticalis (Brischke, 1871) Figs. 41, 120–123. Perilissus verticalis Brischke, 1871: 71. Type lost. Type locality: Poland. Perilissus abdominalis Brischke, 1878: 74. Type lost. Type locality: Poland. Lathrolestus marginatus Thomson, 1883: 917. Holotype ♂, MZLU [examined]. Type locality: Sweden (Skåne, Lund). Material. 1♀, DENMARK, Jutland, Sønderborg, ZMUC; 5♀, 7♂, DENMARK, leg Schiødte, ZMUC; 1♂, FINLAND, Uusikaupunki (“Nystad”), leg. Hellen, MZH; 1♀, FINLAND, Åboland, Pernå, 9.viii.1944, leg Å.Nordström, MZH; 7♀, GENMANY, Northern Germany, ex. Metallus pumilus, xi.1970, leg H.Pschorn-Walcher, SMF; 1♂, RUSSIA, Republic of Karelia, Sortavala, “L.v. Essen”, “3461”, MZH; 1♂, RUSSIA, Leningrad Oblast, Boksitogorsky reg., 20 km S Boksitogorsk, Rgusha riv., viii.2002, leg. A.Reshchikov, NHRS; 2♀, SWEDEN, Skåne, 1907, leg. A. Roman, NHRS; 2♀, SWEDEN, Halland, viii.1922, leg. A. Roman, NHRS; 2♀, 1♂, SWEDEN, Stockholm, leg. C. Boheman, NHRS; 1♀, SWEDEN, Gotland, Visby, Själsö, N57°41.582´E18°21.530´, ... : Published as part of Reshchikov, Alexey, 2015, Review of North European species of the genus Lathrolestes (Hymenoptera, Ichneumonidae) with description of one new species from Öland (Sweden), pp. 1-47 in Zootaxa 4033 (1) on pages 38-40, DOI: 10.11646/zootaxa.4033.1.1, http://zenodo.org/record/289776 ...